Analisis Penerapan Model Pembelajaran Project Based Learning Pada Keaktifan Belajar Peserta Didik Kelas II Sekolah Dasar - Ida Trimuliani; Mira Azizah; Ranto Nety Sofiati; Mei Fita Asri Untari (Journal on Education, 2024)
The aim of this research was to determine the application of the learning model Project Based Learning on active learning. This type of research uses qualitative data collection methods, namely interviews, observation sheets and documentation. The subjects involved in this research were 30 class II students at SD Supriyadi 02 Semarang. The results obtained show that the learning model is applied Project Based Learning able to create student activity during the learning process. In its implementation, students can fulfill the indicators of active learning which consist of (1) discussing with the group; (2) Seriousness in completing the assigned tasks; (3) Asking questions; (4) Expressing opinions; (5) Pay attention to the teacher's explanation. The learning activity of class II students at SD Supriyadi 02 Semarang obtained very good results.